2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26483
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Research Process Sophistication in Engineering Ph.D. Students and the Influence of Prior Experiences

Abstract: focuses on strategies for design innovations through divergent and convergent thinking as well as through deep needs and community assessments using design ethnography, and translating those strategies to design tools and education. She teaches design and entrepreneurship courses at the undergraduate and graduate levels, focusing on front-end design processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For the eight cases in which ratings differed, the PI reviewed the transcripts and made the final determination. More information about these analyses can be found in Mosyjowski et al (2016). For the purposes of this paper, we highlight the features that characterize the responses that make up the most and least sophisticated descriptions of research thinking and note defining characteristics of these categories, as they relate to our findings on the ways students draw on prior experiences to inform their research work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the eight cases in which ratings differed, the PI reviewed the transcripts and made the final determination. More information about these analyses can be found in Mosyjowski et al (2016). For the purposes of this paper, we highlight the features that characterize the responses that make up the most and least sophisticated descriptions of research thinking and note defining characteristics of these categories, as they relate to our findings on the ways students draw on prior experiences to inform their research work.…”
Section: Discussionmentioning
confidence: 99%
“…This section begins with a description of the responses that make up the least sophisticated (Category 1) and most sophisticated (Category 3) categories of research thinking, followed by a discussion of the linkages between the distinguishing characteristics of these emergent levels of research thinking and the prior experiences of returning and direct-pathway students that may contribute. The descriptions of each category come from our team's previous work (Mosyjowski et al, 2016), which also provides examples of participant responses in each category.…”
Section: Sophistication Of Students' Research Thinking and The Role Of Experiencementioning
confidence: 99%
“…This initial study found that the primary value driving returners back to school was utility value, with a lesser emphasis on interest and attainment, and examined the various costs and cost mitigation strategies that returners experience and utilize. Further work, utilizing EVT, was conducted in a nationwide study of engineering returners in doctoral programs [6][7][8][9][10][11][12][13]. This work found similar results for cost categories, compared to earlier work, and provided more insight into the needs of returners in these programs.…”
Section: Returnersmentioning
confidence: 86%
“…[8][9][10][11] This study included both a survey and interviews; the survey provided information to characterize the returners, and to look further at the value of their return to school, using the EVT framework. [8][9][10] The interview phase was designed to learn more about the intersection between work experiences and doctoral research, and at the impact this had on the research process.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The interview phase was designed to learn more about the intersection between work experiences and doctoral research, and at the impact this had on the research process. 11 In addition to these studies specifically on returners, there has been research conducted on the more general population of older, or non-traditional, students. This work covers a variety of different fields, and includes adult students in many different types of degree programs.…”
Section: Introductionmentioning
confidence: 99%